2005
DOI: 10.1038/sj.eye.6702011
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous leptin levels in retinal disease

Abstract: Background/aims The purpose of this study was to investigate the relationship between vitreous leptin levels and retinal diseases. Methods Levels of vitreous leptin were evaluated in proliferative diabetic retinopathy (PDR) and a variety of other retinopathies including: macular disease, neovascular maculopathies, primary retinal detachments, and vascular occlusive disease. Results In patients with PDR (N ¼ 7), the average vitreous level of leptin (37.4 ng/ml) was significantly higher than that in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…In addition, the study suggested that locally produced leptin, not simply leptin derived form circulation, could be involved in the pathogenesis of PDR and RD [31]. Similarly, a small study confirmed higher vitreous leptin levels in PDR relative to other retinopathies [32]. On the other hand, other preliminary analysis involving 25 patients with PDR demonstrated that intravitreous leptin was not directly associated with the disease [33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study suggested that locally produced leptin, not simply leptin derived form circulation, could be involved in the pathogenesis of PDR and RD [31]. Similarly, a small study confirmed higher vitreous leptin levels in PDR relative to other retinopathies [32]. On the other hand, other preliminary analysis involving 25 patients with PDR demonstrated that intravitreous leptin was not directly associated with the disease [33].…”
Section: Introductionmentioning
confidence: 99%
“…42 A total of 24 human vitreous samples (12 non-PVR and 12 PVR) were obtained, with individual sample volumes ranging from 0.6 to 1.3 mL. Samples came from two independent sources: 12 (6 PVR and 6 non-PVR) from patient donors at the Ocular Angiogenesis Group, Department of Ophthalmology Academic Medical Center in Meibergdreef, Amsterdam; and 12 (6 PVR and 6 non-PVR) from patient donors at the Vancouver Hospital in association with the University of British Columbia.…”
Section: Patient Vitreousmentioning
confidence: 99%
“…All subjects underwent a standard three-port vitrectomy, with a core sample of vitreous (1.0 to 1.5 ml) taken before initiating the pars plana infusion as described previously. 26 Undiluted samples were divided into aliquots and stored at Ϫ80°C until use.…”
Section: Rabbit Model For Pvrmentioning
confidence: 99%